COVID-19 and Risk of Acute Ischemic Stroke Among Medicare Beneficiaries Aged 65 Years or Older: Self-Controlled Case Series Study. (22nd February 2022) - Yang, Quanhe; Tong, Xin; George, Mary G.; Chang, Anping; Merritt, Robert K.
Abstract : Background and Objectives: Findings of association between coronavirus disease 2019 (COVID-19) and stroke remain inconsistent, ranging from significant association to absence of association to less than expected ischemic stroke among hospitalized patients with COVID-19. The current study examined the association between COVID-19 and risk of acute ischemic stroke (AIS). Methods: We included 37, 379 Medicare fee-for-service (FFS) beneficiaries aged ≥65 years diagnosed with COVID-19 from April 1, 2020, through February 28, 2021, and AIS hospitalization from January 1, 2019, through February 28, 2021. We used a self-controlled case series design to examine the association between COVID-19 and AIS and estimated the incidence rate ratios (IRRs) by comparing incidence of AIS in risk periods (0–3, 4–7, 8–14, 15–28 days after diagnosis of COVID-19) vs control periods. Results: Among 37, 379 Medicare FFS beneficiaries with COVID-19 and AIS, the median age at diagnosis of COVID-19 was 80.4 (interquartile range 73.5–87.1) years and 56.7% were women. When AIS at day of exposure (day = 0) was included in the risk periods, IRRs at 0–3, 4–7, 8–14, and 15–28 days following COVID-19 diagnosis were 10.3 (95% confidence interval 9.86–10.8), 1.61 (1.44–1.80), 1.44 (1.32–1.57), and 1.09 (1.02–1.18); when AIS at day 0 was excluded in the risk periods, the corresponding IRRs were 1.77 (1.57–2.01) (day 1–3), 1.60 (1.43–1.79), 1.43 (1.31–1.56), and 1.09 (1.01–1.17), respectively. The association appeared to be stronger among younger beneficiaries and among beneficiaries without prior history of stroke but largely consistent across sex and race/ethnicities. Discussion: Risk of AIS among Medicare FFS beneficiaries was 10 times (day 0 cases in the risk period) as high during the first 3 days after diagnosis of COVID-19 as during the control period and the risk associated with COVID-19 appeared to be stronger among those aged 65–74 years and those without prior history of stroke. Classification of Evidence: This study provides Class IV evidence that severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) infection is associated with increased risk of AIS in the first 3 days after diagnosis in Medicare FFS beneficiaries ≥65 years of age.